Inaccuracies in Rogers' History of Prices - Lutz, Harley L. (Quarterly Journal of Economics, 1909)
Journal Article Inaccuracies in Rogers' History of Prices Get access Harley L. Lutz Harley L. Lutz Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 23, Issue 2, February 1909, Pages 350–358, https://doi.org/10.2307/1882805 Published: 01 February 1909